Potential Attack of Rice Field Rat (Rattus argentiventer) on Rice Crops Based on Climate Factors in Karawang Regency, West Java, Indonesia - Aprilia, Lupita; Koesmaryono, Yonny; Priyambodo, Swastiko (Universitas Andalas, 2024)
The production of rice is closely related to the presence of pests, one of which is the rice field rat (Rattus argentiventer). The development of pests that attack plants is influenced by the dynamics of climate factors, both directly and indirectly. The climate in Karawang Regency is highly suitable for the growth of R. argentiventer. In the rice - rice - intercrop cropping pattern, climate factors have strong influence on the infestation of rice field rats during the intercrop season. Meanwhile, climate factors have low influence during the rice monocrop season. Based on CLIMEX output, the altitude difference in Karawang Regency does not have a significant effect on the environment suitability for the growth and development of rice field rats, allowing them to live in any rice field in Karawang Regency. Based on climate scenarios, the suitability of the climate in Karawang Regency for the potential growth and development of rice field rats is projected to decrease in the 2070s. Increasing temperatures and decreasing rainfall cause the rice field rats to experience dry stress.